1993
DOI: 10.1037/0735-7044.107.6.996
|View full text |Cite
|
Sign up to set email alerts
|

Ibotenate lesions of the hippocampus enhance latent inhibition in conditioned taste aversion and increase resistance to extinction in conditioned taste preference.

Abstract: In 2 experiments, the effects of axon-sparing lesions of the hippocampus on performance in aversive and appetitive taste conditioning tasks were investigated. In Experiment 1, hippocampally lesioned rats showed no impairment of conditioned taste aversion learning relative to control subjects, but they did display an increased sensitivity to latent inhibition (LI). In Experiment 2, the same hippocampectomized rats acquired a conditioned taste preference but failed to show any evidence of extinction. The influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 69 publications
(84 reference statements)
14
89
3
Order By: Relevance
“…However, the effects of hippocampal lesions on latent inhibition of conditioned taste aversions are equivocal (McFarland et al, 1978;Reilly et al, 1993;Gallo and Cándido, 1995), which may explain the lack of effect observed in that study. In contrast, the current results are consistent with a disruption in latent inhibition produced by neurotoxic hippocampal lesions in our appetitive within-subject procedure (Han et al, 1995).…”
Section: Behavioral Datacontrasting
confidence: 50%
“…However, the effects of hippocampal lesions on latent inhibition of conditioned taste aversions are equivocal (McFarland et al, 1978;Reilly et al, 1993;Gallo and Cándido, 1995), which may explain the lack of effect observed in that study. In contrast, the current results are consistent with a disruption in latent inhibition produced by neurotoxic hippocampal lesions in our appetitive within-subject procedure (Han et al, 1995).…”
Section: Behavioral Datacontrasting
confidence: 50%
“…This pattern of results has also been observed in rats (Ellenbroek et al 1997;Russig et al 2003). Second, there is increasing evidence that depending on the specific paradigms, the same treatment (drugs, selective brain lesions, or environmental manipulations) can result in differing patterns of LI modulation (Reilly et al 1993;Purves et al 1995;Gallo and Candido 1995;Buhusi et al 1998;Schmajuk et al 2000Schmajuk et al , 2001Oswald et al 2002;Schmajuk 2005;Meyer et al 2006b;Pothuizen et al 2006). Our data (in this paper and in Meyer et al 2004) further indicate that this impression is not unprecedented in either rats or mice.…”
Section: Avoidance Learning After Amphetamine Treatmentsupporting
confidence: 62%
“…4C). Although CTA extinction is attributed primarily to cortical regions, including the PFC (59), studies have indicated that hippocampal lesions slow CTA extinction (29,30), suggesting a potential interaction between the hippocampus and the PFC. Recent studies also suggested that the hippocampus participates in consolidating CTA extinction (60).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that BDNF-KIV mice retain short-term fear extinction but may be inefficient in long-term fear extinction. Finally, we determined whether the extinction deficit extends to conditioned taste aversion (CTA), a process that involves the mPFC (27,28) and hippocampus (29,30). Animals were offered a sweetened solution during a pretraining trial (trial 1: P = 0.52; t test) (Fig.…”
Section: Impairment Of Activity-driven Expression Of Bdnf Protein In Thementioning
confidence: 99%